The emergence of Islamic Banks in Somalia in the post-conflict era: prospects and challenges - Musse, Abdifatah Mohamed; Ab Rashid, Rosemaliza; Zainol, Zairy (OMJP Alpha Publishing, 2019)
Since the collupse of Somalia’s central government in 1991, Somalia experienced an intractable civil war that not only undermined and devastated much of the nations’ social life but also, led to a massive collapse of the country’s financial sector. Nearly a quarter century, Somalia has no functioning financial system due to the conflict and political mayhem. Such circumstances prevented Somalia from developing an effective and coherent financial system. Following the collapse of the country’s institutions, the only financial system that existed during these turbulent times were Xawaalads or money transfer operators mostly founded by Somali diasporas migrated to many countries around the world due to the country’s instability. Another type of informal financial service emerged during the conflict was mobile money or mobile banking operated by giant telecommunication companies in the country. Following the formation of Somalia’s federal government in 2012 and the return of relative normalcy, the major money transfer companies converted to full banking institutions and sought a license from the central bank as full-fledged Islamic financial banks. The purpose of this paper is to explore the emergence of the Islamic banking industry, opportunities and challenges ahead. The paper relied on secondary data obtained from textbooks, journals, newspapers and reports. The study found that Islamic banks in Somalia have potential opportunities but face unique challenges due to the effects of the civil war. The paper also postulates some recommendations for the policymakers to deal with the challenges facing the Islamic banks in Somalia.